2000
DOI: 10.1002/1097-4644(2000)79:1<150::aid-jcb140>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Expression and production of stathmin in growth plate chondrocytes is cell-maturation dependent

Abstract: Growth plate cartilage is comprised of linear columns of chondrocytes with the least differentiated cells at one end and the terminally differentiated cells at the other end. Rat costochondral chondrocytes can be divided into the resting cell zone (reserve cell zone), which contains relatively immature chondrocytes (RC cells), and the phenotypically more mature prehypertrophic and upper hypertrophic cell zones, which together may be termed the growth zone chondrocytes (GC cells). When grown separately in monol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Microtubule system plays a vital role in the cell growth, division, differentiation, secretion and intracellular transportation [3] . Stathmin protein, named as microtubule destablizer due to its important role played in the stability of microtubule system [4] , can disturb the formation of microtubules and influence the assemble of spindles and the development of mitosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microtubule system plays a vital role in the cell growth, division, differentiation, secretion and intracellular transportation [3] . Stathmin protein, named as microtubule destablizer due to its important role played in the stability of microtubule system [4] , can disturb the formation of microtubules and influence the assemble of spindles and the development of mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the inhibition of Stathmin activity resulted in the differentiation of cells. The expression levels of Stathmin were closely related with the proliferation and differentiation of PSCs, even absolutely necessary for cell maturation [3] . By regulating the expression levels of Stathmin gene and modulating the proliferation and differentiation of PSCs, not only large number of seed cells can be obtained for tissue engineering, but also differentiated PSCs can be used to construct epiphyseal plate-like tissue or bone and cartilage, which provided an ideal in vitro and in vivo model for studying many complicated epiphyseal diseases, and the injury of bone and cartilage, and simultaneously provided a novel therapy for these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of p53 generally upregulates p21 WAF1/Cip1 and reduces the expression of stathmin; in such a case, p21 WAF1/Cip1 acts as the transcriptional regulator Steinman et al, 2000;Johnsen et al, 2000). External signals and growth factors like TNFa-, NGF-and EGF-dependent protein kinases are known to lead to stathmin phosphorylation and the associated alterations in MT function, cell cycle, apoptosis and differentiation in various biological systems (Ji et al, 1993;Di Paolo et al, 1996, Vancompernolle et al, 2000Hummert et al, 2000). Induced expression of the catalytic subunit of cAMPdependent protein kinase A also results in increased cellular MT polymer content, phosphorylation and partial degradation of stathmin in K562 cells (Gradin et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in vitro have shown that antisense RNA inhibition of stathmin abrogates the transformed phenotype of K562 leukemia cells (Iancu et al, 2000). Stathmin production and expression is high in immature chondrocytes as compared to the growth zone chondrocytes (Hummert et al, 2000). In consideration of the significant role of stathmin, primarily its association with MT function, cell cycle, differentiation and altered expression in various cancers, elucidation of the nature of its regulatory controls will be useful to discern a variety of cellular signal transduction pathways.…”
Section: Introductionmentioning
confidence: 99%